Chloroprene polymer latex and water-based adhesives
Patent Information
- Application Number
- JP2022177427
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-07-27
- Filing Date
- 2022-11-04
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-11-04
AI Technical Summary
【0010】 本発明によれば、優れた初期接着力及び優れた貯蔵安定性を有する、接着剤用途、特には水性接着剤用途に好適なクロロプレン重合体ラテックス及びこれを用いた水性接着剤が提供される。本発明に係るクロロプレン重合体ラテックス及び水性接着剤は、優れた初期接着力を有し、接着剤使用時に、接着層の乾燥時間を短くし、かつ、乾燥温度を常温とした、湿潤状態であっても、優れた初期接着力を発揮することができる。すなわち、本発明に係るクロロプレン重合体ラテックス組成物及び水性接着剤による接着工程では、従来必要であった、長時間の乾燥や加熱乾燥が必須ではないため、作業工程を短縮することができ、エネルギー及びコストを削減することができ、設備を簡略化することができる。本発明に係るクロロプレン重合体ラテックス組成物及び水性接着剤は、特にポリオレフィン樹脂やポリウレタンフォームの接着に使用されるスプレータイプの接着剤として好適に用いることができる。
Smart Images

Figure 0007943792000001 
Figure 0007943792000002 
Figure 0007943792000003
Abstract
Description
[Technical Field]
[0001] This invention relates to a chloroprene polymer latex composition and an aqueous adhesive using the same. [Background technology]
[0002] Adhesives using chloroprene polymers are used in solvent-based contact adhesives and graft adhesives because they provide high adhesion to various substrates with low pressure. However, solvent-based adhesives are flammable and toxic, and regulations are becoming stricter year by year. In an effort to eliminate solvents, there is a lot of development going on in water-based adhesives using chloroprene polymer latex, but water-based adhesives have lower adhesive strength compared to solvent-based adhesives.
[0003] Therefore, various studies have been conducted to improve the adhesive strength, particularly the initial adhesive strength, of aqueous adhesives using chloroprene polymer latex. For example, two-component adhesives are known in which an adhesion promoter is added to an emulsion-type aqueous adhesive (see Patent Document 1), and two-component adhesives are known in which a composition is mainly composed of a specific chloroprene polymer latex composition, with specific amounts of acrylic latex or SBR latex and an anionic surfactant added, and a polyvalent metal salt is used as a curing agent (see Patent Document 2).
[0004] Furthermore, aqueous adhesives containing a chloroprene polymer latex composition, a polyoxyalkylene alkyl ether sulfate, and a pH adjuster are known (see Patent Document 3), as well as one-component aqueous adhesives containing a chloroprene polymer latex and a specific pH adjuster (see Patent Documents 4 and 5).
[0005] Furthermore, an aqueous adhesive is known that is characterized by containing a specific chloroprene polymer latex, a specific nonionic surfactant, and a pH adjuster (see Patent Document 6). [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 56-59874 [Patent Document 2] Japanese Patent Application Publication No. 9-188860 [Patent Document 3] Japanese Patent Publication No. 2007-332207 [Patent Document 4] International Publication No. 2016 / 133190 [Patent Document 5] International Publication No. 2016 / 133191 [Patent Document 6] Japanese Patent Publication No. 2004-59895 [Overview of the Initiative] [Problems that the invention aims to solve]
[0007] However, with conventional technologies, it was sometimes difficult to achieve both excellent initial adhesive strength and storage stability in chloroprene polymer latex compositions and aqueous adhesives. The present invention aims to provide a chloroprene polymer latex composition that exhibits excellent initial adhesive strength and excellent storage stability, and is suitable for adhesive applications, particularly aqueous adhesive applications, as well as an aqueous adhesive using the same. [Means for solving the problem]
[0008] As a result of diligent research to solve the above problems, the present inventors have found that the above problems can be solved by using a chloroprene polymer latex composition containing a chloroprene polymer and rosin acid and / or an alkali metal salt thereof, and a specific nonionic surfactant, in which the content of the nonionic surfactant is within a specific numerical range.
[0009] The following are examples of various embodiments of the present invention. The embodiments shown below can be combined with each other. [1] A chloroprene polymer latex composition comprising a chloroprene polymer latex and a nonionic surfactant (C) having a cyclic skeleton of a 5-membered or 6-membered ring via an ether group formed by a dehydration reaction of a sugar alcohol, wherein the chloroprene polymer latex comprises a chloroprene polymer (A) with a toluene-insoluble content of 20% by mass or less and rosinic acid and / or its alkali metal salt (B), and the chloroprene polymer latex composition comprises 0.01 to 10 parts by mass of the nonionic surfactant (C) per 100 parts by mass of the solid content of the chloroprene polymer latex. [2] The chloroprene polymer latex composition according to [1], wherein the nonionic surfactant (C) has 5 to 20 polyoxyethylene chains. [3] The chloroprene polymer latex composition according to [1] or [2], wherein the HLB value of the nonionic surfactant (C) is 9 to 17. [4] The chloroprene polymer latex composition according to any one of [1] to [3], further containing 1 to 20 parts by mass of a pH adjusting agent per 100 parts by mass of solids of chloroprene polymer latex contained in the chloroprene polymer latex composition. A water-based adhesive comprising a chloroprene polymer latex composition as described in any of [5][1] to [4]. [Effects of the Invention]
[0010] The present invention provides a chloroprene polymer latex and an aqueous adhesive using the same, which have excellent initial adhesion and excellent storage stability and are suitable for adhesive applications, particularly aqueous adhesive applications. The chloroprene polymer latex and aqueous adhesive according to the present invention have excellent initial adhesion, shorten the drying time of the adhesive layer when using the adhesive, and can exhibit excellent initial adhesion even in a wet state with a drying temperature of room temperature. In other words, in the bonding process using the chloroprene polymer latex composition and aqueous adhesive according to the present invention, long drying times or heat drying that were conventionally required are not necessary, so the work process can be shortened, energy and costs can be reduced, and equipment can be simplified. The chloroprene polymer latex composition and aqueous adhesive according to the present invention can be suitably used as a spray-type adhesive, particularly for bonding polyolefin resins and polyurethane foams. [Modes for carrying out the invention]
[0011] The present invention will be described in detail below. The chloroprene polymer latex composition of the present invention comprises a chloroprene polymer (A), a chloroprene polymer latex containing rosin acid and / or an alkali metal salt thereof (B), and a nonionic surfactant (C) having a cyclic skeleton of a 5-membered or 6-membered ring via an ether group formed by the dehydration reaction of a sugar alcohol, and is characterized by containing the nonionic surfactant (C) in a predetermined proportion. The following describes the components that may be included in the chloroprene polymer latex composition according to the present invention.
[0012] 1. Chloroprene polymer latex The chloroprene polymer latex composition according to the present invention contains chloroprene polymer latex. Furthermore, the chloroprene polymer latex according to the present invention contains chloroprene polymer (A) and rosinic acid and / or its alkali metal salt (B).
[0013] 1.1 Chloroprene polymerization (A) In the present invention, the chloroprene polymer means a polymer containing monomer units derived from 2-chloro-1,3-butadiene (hereinafter also referred to as chloroprene monomer), and includes a homopolymer of the chloroprene monomer, and a copolymer containing monomer units derived from the chloroprene monomer and another monomer copolymerizable with the chloroprene monomer. Examples of the other monomer include 1-chloro-1,3-butadiene, 2,3-dichloro-1,3-butadiene, butadiene, isoprene, styrene, acrylonitrile, acrylic acid and esters thereof, methacrylic acid and esters thereof, and the like.
[0014] The chloroprene polymer latex composition according to one embodiment of the present invention preferably contains 60 to 100 mass% of chloroprene monomer units, when the chloroprene polymer contained in the chloroprene polymer latex composition is taken as 100 mass%. The content of the chloroprene monomer units is, for example, 60, 65, 70, 75, 80, 85, 90, 95, 99, or 100 mass%, and may be within a range between any two of the numerical values exemplified herein.
[0015] The chloroprene polymer latex composition according to one embodiment of the present invention may contain one type of chloroprene polymer, or may contain two or more types of chloroprene polymers. The chloroprene polymer latex composition according to one embodiment of the present invention preferably contains a homopolymer of chloroprene monomer. The chloroprene polymer latex composition according to one embodiment of the present invention preferably contains the homopolymer of chloroprene monomer in an amount of 60 to 100 mass% in terms of solid content, relative to 100 mass% of the solid content of the chloroprene polymer latex contained in the chloroprene polymer latex composition. The content of the homopolymer of chloroprene monomer is, for example, 60, 65, 70, 75, 80, 85, 90, 95, or 100 mass%, and may be within a range between any two of the numerical values exemplified herein. The chloroprene polymer is blended to improve the contact property, heat-resistant adhesive property, and initial adhesive strength of the adhesive using the latex composition.
[0016] <Toluene-insoluble content> The chloroprene polymer contained in the chloroprene polymer latex composition according to the present invention has a toluene-insoluble content (gel content) of 20% by mass or less. In this invention, toluene-insoluble content refers to the gel content of the chloroprene polymer that is insoluble in toluene solvent. Sol refers to components that are soluble in toluene solvent. The excellent initial adhesive strength in this invention is due to the chloroprene polymer containing a large amount of sol with excellent molecular mobility. As a result, fusion of chloroprene polymer molecular chains occurs rapidly at the adhesive interface, adhesive strength is instantaneously developed, and excellent initial adhesive strength is achieved.
[0017] The toluene-insoluble content is, for example, 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20% by mass, and may be within the range of any two of the values exemplified here. If the toluene-insoluble content of the chloroprene polymer exceeds 20% by mass, the initial adhesive strength will decrease, which is undesirable.
[0018] The toluene-insoluble portion can be calculated using the following formula, where A is the mass of the dried product obtained by freeze-drying chloroprene polymer latex, and B is the gel portion separated from the mixture obtained by dissolving the freeze-dried latex in toluene. Specifically, it can be calculated by the method described in the examples. Toluene-insoluble content (gel content) = B / A × 100 (%)
[0019] Toluene-insoluble content can be controlled by adjusting the polymerization conditions during the production of chloroprene polymer latex, such as the type and amount of polymerization initiator and chain transfer agent, as well as the polymerization temperature, polymerization time, polymerization rate, and other production conditions.
[0020] Furthermore, if the chloroprene polymer latex composition contains two or more chloroprene polymers, it is preferable that the toluene-insoluble content contained in the two or more chloroprene polymers (toluene-insoluble content of a mixture of two or more chloroprene polymers) is within the above numerical range.
[0021] 1.2 Rosin acid and / or alkali metal salts thereof (B) Rosin acid or its alkali metal salt (B) is a compound used to emulsion polymerization of chloroprene monomer, and its use improves the initial adhesive strength of the resulting aqueous adhesive. Chloroprene polymer latex containing chloroprene polymer can be prepared as anionic, nonionic, or cationic latex depending on the emulsifiers and dispersants used to emulsion polymerization of the monomers. When used as a raw material for adhesives, anionic latex is preferred from the viewpoint of improving initial adhesive strength. Anionic latex is a latex obtained by emulsion polymerization of monomers using mainly anionic emulsifiers and dispersants.
[0022] The most preferred emulsifier and dispersant for anionic latex is rosin acid and / or its alkali metal salt, and the chloroprene polymer latex according to the present invention contains rosin acid and / or its alkali metal salt. The rosin acid can include wood's rosin acid, gum rosin acid, tall rosin acid, or disproportionated rosin acids thereof. Emulsification polymerization using rosin acid is often carried out under strongly alkaline conditions, and in strongly alkaline chloroprene polymer latex, rosin acid exists in the form of an alkali metal salt. Examples of compounds constituting the alkali metal salt include potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, potassium bicarbonate, and sodium bicarbonate.
[0023] The chloroprene polymer latex composition according to the present invention preferably contains 0.5 to 10 parts by mass, and more preferably 2 to 6 parts by mass, of rosin acid and / or its alkali metal salt per 100 parts by mass of the solid content of the chloroprene polymer contained in the chloroprene polymer latex composition. The content of rosin acid and / or its alkali metal salt may be, for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 parts by mass, and may be within the range of any two of the values exemplified here. If the amount is less than 0.5 parts by mass, emulsification failure is likely to occur, leading to problems such as deterioration of polymerization heat control, formation of aggregates, and poor product appearance. If the amount exceeds 10 parts by mass, residual emulsifier can worsen the water resistance of the polymer, leading to problems such as decreased adhesive strength, foaming during drying, and deterioration of product color.
[0024] The chloroprene polymer latex composition according to one embodiment of the present invention may contain emulsifiers and dispersants other than rosin acid and / or its alkali metal salts. These emulsifiers and dispersants will be described later in the explanation of the method for producing chloroprene polymer latex.
[0025] 1.3 Method for producing chloroprene polymer latex The method for producing the chloroprene polymer latex according to the present invention is not particularly limited, but it can be produced by the following method. A method for producing chloroprene polymer latex according to one embodiment of the present invention may include an emulsion polymerization step, in which a chloroprene monomer, or a chloroprene monomer and other monomer copolymerizable therewith, is emulsion polymerized using an emulsifier, a dispersant, a polymerization initiator, a chain transfer agent, etc. as appropriate, and when the desired polymerization rate is reached, a polymerization inhibitor is added to obtain chloroprene polymer latex. Furthermore, unreacted monomers can be removed from the chloroprene polymer latex obtained in this manner by methods such as steam flushing or concentration.
[0026] (emulsifier) The emulsifier preferably contains rosin acid and / or its alkali metal salt. Alternatively, emulsifiers and dispersants other than rosin acid and / or its alkali metal salt can be used in combination. The amount of rosin acid and / or its alkali metal salt added is preferably 0.5 to 10 parts by mass, and more preferably 2 to 6 parts by mass, per 100 parts by mass of the total monomer used. The amount of rosin acid and / or its alkali metal salt added may be, for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 parts by mass, and may be within the range of any two of the values exemplified here. If the amount is less than 0.5 parts by mass, emulsification failure is likely to occur, leading to problems such as poor control of polymerization heat generation, formation of aggregates, and poor product appearance. If the amount exceeds 10 parts by mass, residual emulsifier can worsen the water resistance of the polymer, leading to problems such as reduced adhesive strength, foaming during drying, and deterioration of product color.
[0027] In the emulsion polymerization process, emulsifiers and dispersants other than rosin acid and / or its alkali metal salts can also be used, and anionic emulsifiers and dispersants are preferred among them. When adding pH adjusters, it is preferable to use sulfate-based or sulfonate-based anionic emulsifiers and dispersants in combination with the anionic emulsifiers and dispersants other than rosin acid and / or its alkali metal salts in order to stabilize the chloroprene polymer latex. Examples of anionic emulsifiers and dispersants other than rosin acid and / or its alkali metal salts include alkyl sulfonates with 8 to 20 carbon atoms, alkylaryl sulfates, condensates of sodium naphthalene sulfonate and formaldehyde, and sodium alkyldiphenyl ether disulfonate. The amount of emulsifiers and dispersants other than rosin acid and / or its alkali metal salts added is preferably 0.05 to 5 parts by mass, and more preferably 0.1 to 2 parts by mass, per 100 parts by mass of the total monomer used.
[0028] (Chain transfer agent) During emulsion polymerization of chloroprene monomers, it is preferable to add a chain transfer agent to adjust the molecular weight, molecular weight distribution, and toluene-insoluble content of the chloroprene polymer. The chain transfer agent may be added at the beginning of polymerization or during polymerization. Preferred chain transfer agents include long-chain alkyl mercaptans such as n-dodecyl mercaptan and t-dodecyl mercaptan, and dialkyl xanthogen disulfides such as diisopropyl xanthogen disulfide and diethyl xanthogen disulfide. Long-chain alkyl mercaptans are more preferable because they allow for easier control of molecular weight and toluene-insoluble content. There is no problem in using two or more of these chain transfer agents in combination. The total amount of chain transfer agent added during emulsion polymerization is preferably 0.005 to 0.12 parts by mass per 100 parts by mass of the chloroprene polymer and monomer copolymerizable with the chloroprene monomer. The total amount of chain transfer agent added may be, for example, 0.005, 0.01, 0.05, 0.1, 0.11, or 0.12 parts by mass, and may be within the range of any two of the values exemplified here.
[0029] (Initiator) Conventional radical polymerization initiators can be used as polymerization initiators. Specifically, organic or inorganic peroxides such as benzoyl peroxide, potassium persulfate, and ammonium persulfate, and azo compounds such as azobisisobutyronitrile can be used. Co-catalysts such as anthraquinone sulfonates, potassium sulfite, and sodium sulfite may also be used as appropriate.
[0030] (Potassium hydroxide and sodium hydroxide) In the emulsion polymerization process, sodium hydroxide and / or potassium hydroxide can be used. The amount of sodium hydroxide and potassium hydroxide added can be 0.01 to 2.0 parts by mass per 100 parts by mass of monomer.
[0031] (polymerization rate) The polymerization conversion rate of chloroprene monomers during emulsion polymerization of chloroprene polymers is preferably 50% by mass or more and less than 90% by mass, and more preferably 60% to 85% by mass. If the polymerization conversion rate is less than 50%, the solid content concentration of the chloroprene polymer latex decreases, which can put a load on the drying process after adhesive application, make it difficult to homogenize the adhesive layer, and worsen odor, tackiness, and adhesive strength due to residual chloroprene monomers. If the polymerization conversion rate is 90% by mass or more, the branching in the chloroprene polymer may increase, or the molecular weight distribution may broaden due to the increase in molecular weight, which can worsen the initial adhesive strength, an important performance characteristic in this invention. The polymerization conversion rate (by mass%) is calculated by [(total polymer mass / total monomer mass) × 100]. Hereinafter, the polymerization conversion rate may simply be referred to as the polymerization rate.
[0032] (Polymerization temperature) Chloroprene polymers can be polymerized in the range of 0 to 45°C, but low-temperature polymerization at 5 to 20°C is particularly preferred. Trans-1-4 bonds typically account for more than 85%, and the molecular structure is relatively regular. Due to this high degree of regularity in the molecular structure, chloroprene polymers possess the properties of a typical crystalline polymer. Polymerization at low temperatures, particularly 5 to 20°C, further increases the proportion of trans-1-4 bonds within the polychloroprene molecule, thereby increasing the crystallization rate and achieving sufficient adhesive strength when used as an aqueous adhesive.
[0033] (Polymerization inhibitor) Generally, in the production of chloroprene polymers, a polymerization inhibitor is added to stop the reaction when a predetermined polymerization rate is reached, in order to obtain a polymer with a desired molecular weight and distribution. There are no particular restrictions on the polymerization inhibitor, but specific examples include phenothiazine, pt-butylcatechol, hydroquinone, hydroquinone monomethyl ether, and diethylhydroxylamine.
[0034] (solid content concentration) The solid content concentration of chloroprene polymer latex is not particularly limited, but is usually 40-65% by mass. The solid content concentration of chloroprene polymer latex can be controlled by adjusting the mixing ratio of solvents such as water during the emulsion polymerization of the chloroprene polymer, or by evaporating the water contained in the chloroprene polymer latex under reduced pressure.
[0035] 2. Nonionic surfactant (C) The chloroprene polymer latex composition of the present invention contains a nonionic surfactant in addition to anionic emulsifiers and dispersants. In the present invention, by including a specific amount of a nonionic surfactant (C) with a specific structure, the storage stability of the latex and the adhesive properties when used as an adhesive can be improved.
[0036] The chloroprene polymer latex composition according to the present invention comprises a nonionic surfactant (C) having a five-membered or six-membered cyclic skeleton via an ether group formed by the dehydration reaction of a sugar alcohol. Examples of sugar alcohols include sorbitol. The nonionic surfactant (C) preferably has a five-membered or six-membered cyclic skeleton via an ether group. In addition, the nonionic surfactant (C) according to one embodiment of the present invention may be a mixture of forms having a five-membered cyclic skeleton and forms having a six-membered cyclic skeleton, or both may be mixed in equilibrium. That is, the nonionic surfactant (C) according to one embodiment of the present invention includes a form having a five-membered cyclic skeleton, a form having a six-membered cyclic skeleton, and a form in which both are mixed.
[0037] The nonionic surfactant (C) preferably contains polyoxyethylene chains, that is, it preferably contains repeating units represented by (CH2CH2O). Furthermore, it is desirable that the nonionic surfactant (C) has 5 to 20 polyoxyethylene chains. The number of polyoxyethylene chains refers to the total number of repeating units represented by (CH2CH2O) contained in the nonionic surfactant (C). For example, if the nonionic surfactant (C) contains polyoxyethylene chains (CH2CH2O)a, (CH2CH2O)b, and (CH2CH2O)c in its molecule (where a, b, and c are the number of repeating (CH2CH2O) units in each polyoxyethylene chain), the number of polyoxyethylene chains of the nonionic surfactant (C) is a + b + c. The polyoxyethylene chain number can be, for example, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20, and may be within the range of any two of the values exemplified here.
[0038] Furthermore, the HLB value of nonionic surfactants is preferably in the range of 9 to 17. Examples of HLB values include 9, 10, 11, 12, 13, 14, 15, 16, and 17, and may also be within the range of any two of the values exemplified here. By using a nonionic surfactant (C) whose polyoxyethylene chain number and HLB value meet these ranges, the initial adhesive strength of the resulting aqueous adhesive is further improved.
[0039] The nonionic surfactant (C) can be a polyoxyethylene sorbitan fatty acid ester. The fatty acid can be either a saturated or unsaturated fatty acid. The nonionic surfactant (C) preferably contains a structure derived from a fatty acid. The fatty acid preferably has 8 to 24 carbon atoms, for example, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, or 24, and may be within the range of any two of the values exemplified here. Nonionic surfactants (C) can be compounds represented by the following formula (C).
[0040] [ka]
[0041] In equation (C), R 1 ~R 4 R can be a hydrogen atom, an optionally substituted alkenyl group, or an optionally substituted alkyl group. 1 ~R 4 However, if it is an alkenyl group which may have substituents or an alkyl group which may have substituents, it is more preferable that it has 8 to 24 carbon atoms. 1 ~R 4 However, in the case of an alkenyl group that may have substituents or an alkyl group that may have substituents, the number of carbon atoms may be, for example, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, and may be within the range of any two of the numbers exemplified here. 1 ~R 4 These may have the same structure or they may have different structures. Furthermore, the sum of a+b+c, i.e., the polyoxyethylene chain number, is preferably between 5 and 20. The polyoxyethylene chain number of a+b+c is, for example, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20, and may be within the range of any two of the values exemplified here.
[0042] The amount of nonionic surfactant (C) added is 0.01 to 10 parts by mass, preferably 0.05 to 5 parts by mass, per 100 parts by mass of solids of chloroprene polymer latex. If the content of nonionic surfactant (C) is less than 0.01 parts by mass, it tends to contribute to the storage stability and adhesive properties that are the effects of adding nonionic surfactant. If it exceeds 10 parts by mass, when used as an adhesive, problems such as a decrease in adhesive strength and water resistance, and deterioration of the product's color tone are likely to occur due to a large amount of surfactant remaining. The content of nonionic surfactant (C) may be, for example, 0.01, 0.05, 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 parts by mass, and may be within the range of any two of the values exemplified here.
[0043] The nonionic surfactant can be added either during polymerization or when the adhesive is mixed. Furthermore, the chloroprene polymer latex composition according to one embodiment of the present invention may also contain nonionic surfactants other than nonionic surfactant (C) to the extent that they do not impair the effects of the present invention.
[0044] 3. pH adjusters A chloroprene polymer latex composition according to one embodiment of the present invention may contain a pH adjuster. The pH adjuster is added to improve the initial adhesive strength and storage stability when the chloroprene polymer latex composition is used as an aqueous adhesive. Weak acids and buffer solutions can be used as pH adjusters. Specifically, at least one compound selected from hydroxy acids such as citric acid and glycolic acid, boric acid, and amino acids is desirable, with amino acids being particularly preferred. Examples of amino acids include glycine, alanine, threonine, and proline, but glycine is more preferred due to its cost, adhesive performance, and ease of handling.
[0045] The chloroprene polymer latex composition according to one embodiment of the present invention preferably contains 1 to 20 parts by mass of a pH adjusting agent per 100 parts by mass of solids of chloroprene polymer latex contained in the chloroprene polymer latex composition. The content of the pH adjusting agent may be, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20 parts by mass, and may be within the range of any two of the values exemplified herein.
[0046] 4. Plasticizers A chloroprene polymer latex composition according to one embodiment of the present invention may contain a plasticizer. The amount of plasticizer added is 0.1 to 30 parts by mass, preferably 1 to 20 parts by mass, and more preferably 2 to 15 parts by mass, per 100 parts by mass of solids of the chloroprene polymer latex. The plasticizer content may be, for example, 0.1, 0.2, 0.5, 1, 5, 10, 15, 20, 25, or 30 parts by mass, and may be within the range of any two of the values exemplified here. By adding a plasticizer, the initial adhesive strength of the aqueous adhesive containing the resulting chloroprene polymer latex is improved, and the texture of the adhesive film after drying can be made softer. In particular, it is preferable to add a plasticizer when using it as an adhesive for polyurethane foam. The plasticizer should preferably have good compatibility with the chloroprene polymer, and is not particularly limited, but examples include dibutyl sebacate, dibutyl phthalate, dioctyl adipate, dioctyl azelate, dioctyl sebacate, dioctyl phthalate, tricresyl phosphate, cresyl diphenyl phosphate, etc.
[0047] 5. Other ingredients Chloroprene polymer latex compositions are generally susceptible to degradation by oxygen. In this invention, stabilizers such as antioxidants can be appropriately used in the aqueous adhesive, as long as they do not impair the effects of the invention.
[0048] When an antioxidant is added to a chloroprene polymer latex composition, particularly an aqueous adhesive, the amount of antioxidant added is preferably 0.1 to 3 parts by mass of antioxidant per 100 parts by mass of solids of the chloroprene polymer latex. Setting the amount within this range improves the time-dependent stability of the flexibility of the resulting adhesive layer. If the antioxidant is insoluble in water or destabilizes the emulsified state of the chloroprene polymer latex composition, it is preferable to prepare it as an aqueous dispersion beforehand before adding it. The polychloroprene latex adhesive according to one embodiment of the present invention may not contain an antioxidant.
[0049] In the chloroprene polymer latex composition of the present invention, particularly in aqueous adhesives, fillers, tackifiers, pigments, colorants, wetting agents, defoamers, thickeners, etc., may be used as additives other than those mentioned above, as long as they do not impair the effects of the present invention. In addition, other resin emulsions (latex) may be added as auxiliary ingredients, up to a maximum of 30% by mass (on a solid content basis) of the total composition. Specifically, examples of resin emulsions include (modified) vinyl acetate, vinyl acetate / acrylic mixtures, acrylic / styrene mixtures, and urethane.
[0050] 6. Chloroprene polymer latex composition and aqueous adhesive The chloroprene polymer latex composition according to the present invention comprises chloroprene polymer latex and a nonionic surfactant (C), and can further contain the above-mentioned additives, and can be used as an aqueous adhesive.
[0051] The chloroprene polymer latex composition and aqueous adhesive according to the present invention preferably have the following properties. The chloroprene polymer latex composition and water-based adhesive according to one embodiment of the present invention preferably have an initial adhesive force evaluated under the following conditions, that is, the shortest standing time (open time) until a specific adhesive property is developed is 6 minutes or less. The shortest standing time (open time) until a specific adhesive property is developed is, for example, 0.1, 0.5, 1, 2, 3, 4, 5, 6 minutes, and may be within a range between any two of the numerical values exemplified here.
[0052] [Initial Adhesive Force] A 250×80 mm surface of a urethane foam EMO (manufactured by Inoac Corporation, trade name) cut to 250×80×35 mm was used as the application surface. Both ends of the 250 mm side were masked to set the application area to 140×80 mm, and then the water-based adhesive was sprayed at 100 g / m 2 and applied, followed by standing for a certain period of time in an atmosphere at 20°C. The applied surface is folded into a U-shape so as to face inward, bonded for 5 seconds to such an extent that the urethane foam is not deformed, then released, and it is observed whether the state can be maintained. The shortest standing time (open time [minutes]) until no peeling occurs after 5 seconds and the adhesive property is developed is taken as the evaluation index.
[0053] For the chloroprene polymer latex composition and water-based adhesive according to one embodiment of the present invention, when storage stability is evaluated under the following conditions, the evaluation of appearance and viscosity change after 1 week is preferably ○ or ◎, the evaluation of appearance and viscosity change after 2 weeks is preferably ○ or ◎, and the evaluation of appearance and viscosity change after 4 weeks is preferably ○ or ◎.
[0054] [Storage Stability] 235 g of the water-based adhesive is placed in a glass container with a body diameter of 19.5 cm and a capacity of 225 mL, which is then tightly sealed. This is stored at 40°C, and the appearance and viscosity change after 1 week, 2 weeks, and 4 weeks are recorded. Samples with no change in appearance or viscosity are rated as ◎, samples with slight viscosity change are rated as ○, samples with viscosity change, formation of a film or a small amount of aggregates are rated as △, and samples with significant viscosity change, separation of the added surfactant, or coagulation of the adhesive are rated as ×.
[0055] The aqueous adhesive according to one embodiment of the present invention can be a one-component aqueous adhesive. Suitable adherends for the aqueous adhesive according to one embodiment of the present invention are foams made of materials such as polyurethane, ethylene-vinyl acetate copolymer, and polyethylene, or absorbent adherends such as wood, cloth, and textiles.
[0056] Chloroprene polymer latex compositions containing chloroprene polymer latex manufactured under the various conditions described above are suitable for use as aqueous adhesives, particularly one-component aqueous adhesives, possessing excellent initial adhesion and contact properties, water resistance, spray coating properties, and storage stability. [Examples]
[0057] The present invention will be described in more detail below with reference to examples. These examples are not intended to limit the present invention. In the following examples, parts and percentages are by mass unless otherwise specified.
[0058] [Chloroprene polymer latex] For Examples 1-10 and Comparative Examples 1-8, the following latexes were used, respectively. The solids content and toluene-insoluble content of the obtained latexes were measured using the following procedure.
[0059] (Manufacturing of chloroprene polymer latex A) Using a 10-liter reactor, under a nitrogen atmosphere, 90 parts by mass of water, 4.5 parts by mass of disproportionated rosinic acid, 0.7 parts by mass of potassium hydroxide, and 0.3 parts by mass of sodium salt of formaldehyde-naphthalene sulfonic acid condensate were charged. After dissolution, 100 parts by mass of chloroprene monomer and 0.1 parts by mass of n-dodecyl mercaptan were added while stirring. Potassium persulfate was used as an initiator, and polymerization was carried out at 10°C under a nitrogen atmosphere. When the polymerization rate reached 83%, an emulsion of phenothiazine was added to stop the polymerization. Unreacted chloroprene monomers were removed under reduced pressure to obtain chloroprene polymer latex. Further water evaporation under reduced pressure was performed to concentrate the mixture, and the solid content was adjusted to 55% by mass.
[0060] (Manufacturing of chloroprene polymer latex B) Using a 10-liter reactor, under a nitrogen atmosphere, 90 parts by mass of water, 4.5 parts by mass of disproportionated rosinic acid, 0.5 parts by mass of potassium hydroxide, and 0.3 parts by mass of sodium salt of formaldehyde naphthalene sulfonic acid condensate were charged. After dissolution, 100 parts by mass of chloroprene monomer and 0.05 parts by mass of n-dodecyl mercaptan were added while stirring. Potassium persulfate was used as an initiator, and polymerization was carried out at 10°C under a nitrogen atmosphere. When the polymerization rate reached 70%, an emulsion of phenothiazine was added to stop the polymerization. Unreacted chloroprene monomers were removed under reduced pressure to obtain chloroprene polymer latex. Further water evaporation under reduced pressure was performed to concentrate the mixture, and the solid content was adjusted to 55% by mass.
[0061] (Manufacturing of chloroprene polymer latex C) Using a 10-liter reactor, under a nitrogen atmosphere, 100 parts by mass of water, 4 parts by mass of disproportionated rosinic acid, 0.6 parts by mass of sodium hydroxide, 0.5 parts by mass of potassium hydroxide, 0.3 parts by mass of sodium salt of formaldehyde naphthalene sulfonic acid condensate, and 0.3 parts by mass of sodium bisulfite were charged. After dissolution, 100 parts by mass of chloroprene monomer and 0.14 parts by mass of n-dodecyl mercaptan were added while stirring. Potassium persulfate was used as an initiator, and polymerization was carried out at 10°C under a nitrogen atmosphere. When the polymerization rate reached 90%, an emulsion of phenothiazine was added to stop the polymerization. Unreacted chloroprene monomers were removed under reduced pressure to obtain chloroprene polymer latex. Further water evaporation under reduced pressure was performed to concentrate the mixture, and the solid content was adjusted to 50% by mass.
[0062] (Manufacturing of chloroprene polymer latex D) Using a 10-liter reactor, 106.3 parts by mass of water, 3.5 parts by mass of polyvinyl alcohol, 2.0 parts by mass of methacrylic acid, and 0.1 parts by mass of sodium sulfite were charged under a nitrogen atmosphere. After dissolution, 39.2 parts by mass of chloroprene and 0.1 parts by mass of octyl mercaptan were added while stirring. Potassium persulfate was used as an initiator, and polymerization was carried out at 35°C under a nitrogen atmosphere. When the polymerization rate reached 15%, 58.5 parts by mass of chloroprene and 0.15 parts by mass of octyl mercaptan were continuously added. When the polymerization rate reached 98%, an emulsion of phenothiazine was added to stop the polymerization. After adjusting the pH to 7.2 with a 45% diethanolamine aqueous solution, unreacted chloroprene monomers were removed under reduced pressure to obtain chloroprene polymer latex. Water was added to adjust the solid content concentration to 50% by mass.
[0063] [Solid content] The mass of the aluminum dish alone was denoted as ag, the mass of the aluminum dish containing 2 mL of chloroprene polymer latex sample as bg, and the mass of the aluminum dish containing the latex sample after drying at 125°C for 1 hour as cg. The mass was calculated using the following formula (1).
[0064] Solid content concentration [%] = {(ca) / (ba)} × 100 ···(1)
[0065] [Toluene-insoluble content] After freeze-drying each sample, it was accurately weighed to X g. This was dissolved in toluene (adjusted to 0.6%), centrifuged, and the gel component was separated using a 200-mesh wire mesh. The separated gel component was air-dried, then dried at 110°C for 1 hour, and its mass was accurately weighed to Y g. The gel content was calculated using the following formula (2). Note that by performing the same procedure with a chloroprene polymer latex composition as the analyte, the toluene-insoluble portion of the chloroprene polymer contained in the chloroprene polymer composition can be evaluated.
[0066] Toluene-insoluble content [%] = (Y / X) × 100 ... (2)
[0067] [Nonionic surfactants] The nonionic surfactants used in the aqueous adhesive compositions of the examples and comparative examples were as follows: a. Leodor TW-L106 (manufactured by Kao Corporation, polyoxyethylene sorbitan monolaurate, polyoxyethylene chain count = 6, HLB = 13.3) b. Leodor TW-L120 (manufactured by Kao Corporation, polyoxyethylene sorbitan monolaurate, polyoxyethylene chain count = 20, HLB = 16.7) c. Leodor TW-O106V (manufactured by Kao Corporation, polyoxyethylene sorbitan monooleate, polyoxyethylene chain count = 6, HLB = 10.0) d. Leodor TW-O320V (manufactured by Kao Corporation, polyoxyethylene sorbitan trioleate, polyoxyethylene chain count = 20, HLB = 11.0) e. Neugen EA-137 (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., polyoxyethylene styrene-phenyl ether, HLB=13.0) f. Emulgen 109P (manufactured by Kao Corporation, polyoxyethylene lauryl ether, polyoxyethylene chain number = 9, HLB = 13.6) g. Emulgen 103 (manufactured by Kao Corporation, polyoxyethylene lauryl ether, polyoxyethylene chain number = 3, HLB = 8.1)
[0068] [Preparation of one-component water-based adhesive] To 100 parts by mass of the chloroprene polymer latex obtained above, 5 parts by mass of dibutyl sebacate, 6 parts by mass of glycine, and various surfactants were mixed using a Three One Motor in the ratios shown in Table 1 to prepare an aqueous adhesive. The initial adhesive strength and storage stability of the obtained one-component aqueous adhesive were measured by the following method, and the measurement results are shown in Tables 1 and 2.
[0069] [Initial adhesive strength] A 250 x 80 mm side of a 250 x 80 x 35 mm piece of urethane foam EMO (manufactured by Inoac Corporation, product name) was used as the coating surface. After masking both ends of the 250 mm side to create a coating area of 140 x 80 mm, a water-based adhesive was sprayed on at a rate of 100 g / m². 2 The material was applied and left for a certain period of time in a 20°C atmosphere. The material was folded into a U-shape with the applied surface facing inward, and bonded for 5 seconds to the extent that the urethane foam did not deform. After releasing, it was observed whether the state could be maintained. If peeling did not occur after 5 seconds, the shortest standing time (open time [minutes]) until the adhesive properties were established was used as the evaluation index.
[0070] [Storage stability] 235g of water-based adhesive was placed in a glass container with a diameter of 19.5cm and a capacity of 225mL, and sealed tightly. This was stored at 40°C, and the changes in appearance and viscosity were recorded after 1 week, 2 weeks, and 4 weeks. ◎ indicated no change in appearance or viscosity, ○ indicated a slight change in viscosity, △ indicated a change in viscosity or the formation of a film or small amount of aggregates, and × indicated a significant change in viscosity, separation of the added surfactant, or solidification of the adhesive. In Comparative Example 6, the surfactant and latex were incompatible, so it was evaluated as ×.
[0071] [Table 1]
[0072] [Table 2]
Claims
1. A chloroprene polymer latex composition comprising a chloroprene polymer latex and a nonionic surfactant (C) having a cyclic skeleton of a five-membered or six-membered ring via an ether group formed by the dehydration reaction of a sugar alcohol, The chloroprene polymer latex comprises a chloroprene polymer (A) with a toluene-insoluble content of 20% by mass or less, and rosinic acid and / or its alkali metal salt (B). The chloroprene polymer latex composition comprises 0.01 to 10 parts by mass of the nonionic surfactant (C) per 100 parts by mass of the solid content of the chloroprene polymer latex. The chloroprene polymer latex composition has a solid content of 30% by mass or less of the chloroprene polymer other than the chloroprene polymer, relative to 100% by mass of the chloroprene polymer latex composition. The aforementioned other resin emulsion is at least one selected from (modified) vinyl acetate, vinyl acetate / acrylic mixture, acrylic / styrene mixture, and urethane, in a chloroprene polymer latex composition.
2. A chloroprene polymer latex composition according to claim 1, for use as an aqueous adhesive.
3. The chloroprene polymer latex composition according to claim 1 or claim 2, wherein the nonionic surfactant (C) has 5 to 20 polyoxyethylene chains.
4. The chloroprene polymer latex composition according to claim 1 or claim 2, wherein the HLB value of the nonionic surfactant (C) is 9 to 17.
5. The chloroprene polymer latex composition according to claim 1 or claim 2, further containing 1 to 20 parts by mass of a pH adjusting agent per 100 parts by mass of solids of the chloroprene polymer latex contained in the chloroprene polymer latex composition.
6. An aqueous adhesive comprising the chloroprene polymer latex composition according to claim 1 or claim 2.
Citation Information
Patent Citations
Neoprene latex adhesive for mica tape and preparation method of neoprene latex adhesive
CN113881368A
Flame retardant compositions
GB1306838A
Twoopack adhesive
JP1981059874A
Chloroprene copolymer composition, its production and adhesive
JP1989284544A
Adhesive for rubber
JP1991122184A
